Interview with Benjamin Sovacool - Benjamin K. Sovacool (economic sociology_the european electronic newsletter, 2020)
What was your motivation when you started thinking about a new journal on social science research on energy? - I wish I could give you an elegant grand answer that the motivation was to create a better world or to convince policy makers. But actually, it was a very strategic move of people in the energy studies field - people who study energy supply, energy use, energy demand. We had a whole family of journals that we could publish in, but even the so-called social science journals which had names like Energy Policy weren't very social science-oriented. [...]
Keywords: 300